1063 Cerebellar and Thalamic Growth in Preterm Infants in Relation to Birth Weight (BW). (October 2012) - Andrew, E; Siu, J; Pelling, VJ; Rabe, H; Amess, P; Alvarez, JR Fernandez
Abstract : Background: Reduced cerebellar/thalamic growth affects neurodevelopment. The exact mechanisms are unknown. Aims: To compare cerebellar/thalamic growth of preterms in relation to BW and weight at 36 weeks' corrected (W36). Methods: Retrospective matched cohort-analysis: 4 BW groups matched for maternal smoking, chorioamnionitis, antenatal steroids, delivery mode, multiples and gender. Exclusions growth restriction, congenital anomalies. Study variables (table1 ) gestational age (GA), BW, W36, head circumference at birth/36 weeks (HC/HC36), transverse cerebellar/thalamic diameter at birth/36 weeks (TCD/TTD and TCD36/TTD36). Confounding variables ventilation days (V), oxygen requirement 36 weeks' corrected (O2 ), postnatal steroids (PS), NEC, days antibiotic treatment (ABX), days parenteral nutrition (TPN), phototherapy, IVH, PVL. Statistics median (quartiles, 25 th /75 th ), Friedman-/Cochran-Test. There was a statistically significant difference in V, PS, O2, ABX, TPN, but not NEC, phototherapy, IVH, PVL. Conclusion: Cerebellar growth is more resilient than thalamus or cerebrum to the negative effects of established risk factors for poor neurodevelopmental outcome.